Tribunal Constitucional del Perú y conflicto de poderes - Huerta Guerrero, Luis Alberto (2023)
In Peru, the Constitutional Court has jurisdiction to resolve unconstitutionality and conflicts processes in a single instance, and must do so through the interpretation of constitutional norms, as it is the highest body of control and interpretation of the Constitution. This research analyzes the position assumed by the Court in the face of conflicts between Congress and the Executive Power during the unstable political period 2016-2021. In the control of the laws and the modifications to the Rules of Congress approved by the parliamentary majorities elected in 2016 and 2020, the dissolution of Congress decreed on September 30, 2019 by the Executive and the vote of confidence, established important guidelines of constitutional interpretation; however, this did not occur in matters such as the control of the presidential vacancy due to permanent moral incapacity, the extraordinary emergency decrees issued by the Government while the dissolution of Congress lasted and the rules incorporated in the New Constitutional Procedural Code on votes in the Court for the resolution of constitutional processes.